Penerapan Aplikasi E-Cuti Berbasis Web Dengan Extreme Programming (Studi Kasus: Pengadilan Agama Jakarta Barat) - Agung Siswopranoto; Galuh Saputri (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT The West Jakarta Religious Court is one of the divisions of the Supreme Court of the Republic of Indonesia, now the leave process at the West Jakarta Religious Court is conventional or in the sense of the word manual. From the results of my observations at the West Jakarta Religious Court, employees need to take a leave application form at the personnel division. After that, the employee needs to fill out a form and ask for a signature from the Head of Sub-Division of each division to obtain leave permission. Then from the Head of the Sub-Division continued by asking for the signature of the Head of the West Jakarta Religious Court. After obtaining signatures from the West Jakarta Religious Court, the form is continued back to the Head of Personnel Sub-Section to recap data and reduce the employee's remaining leave. Based on this problem, a solution is proposed to overcome this problem, namely by creating a Web-based employee E-Leave application at the West Jakarta Religious Court, using the PHP programming language and MySQL database, as well as a software development method using Extreme Programming. Testing on the E-Leave application used ISO 25010 with two aspects of testing, namely the functionality usability aspect and obtaining 100% results and the operability aspect obtaining 85.24% results. Keyword: West Jakarta PA Leave, Extreme Programming, Web, ISO 25010